2020
DOI: 10.1016/j.jeurceramsoc.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Creep behavior identification of an environmental barrier coating using full-field measurements

Abstract: For the use of thermal and environmental barrier coating (T/EBC) with ceramic matrix composites, it is crucial to master the behavior under (extreme) environments representative of the hot section of engine turbines. An experimental setup to simulate such thermal loading has been developed with various diagnostics enabling for kinematic and thermal field measurements, which are used to drive a finite element model and estimate thermomechanical properties such as creep parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…74 NASA's Laser Steady-State Heat Flux Thermal Conductivity Testing is a representative steady approach for thermal conductivity test of T/EBCs. 49,75 Samples were heated up by a pulse laser. The heat flux and temperature variations with time at both the coating surface and backside were recorded.…”
Section: Thermal Conductivitymentioning
confidence: 99%
See 3 more Smart Citations
“…74 NASA's Laser Steady-State Heat Flux Thermal Conductivity Testing is a representative steady approach for thermal conductivity test of T/EBCs. 49,75 Samples were heated up by a pulse laser. The heat flux and temperature variations with time at both the coating surface and backside were recorded.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…The maximum temperature can reach to more than 1400 • C. They concluded that uniform, dense, and composition gradient mullite by CVD showed superior adherent with CMCs substrates and comparable thermal shock resistance with Si/mullite/YSZ triple-layer structure by APS. 75 Laser has highly concentrated energy and can heat a small local area to a very high temperature within a very short time. Laser on and off can achieve fast heating and cooling conditions for samples.…”
Section: Thermal Shockmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from tensile tests carried out at room temperature were used. Archer et al [36] also proposed a FEMU-based approach to calibrate creep parameters of an environmental barrier coating. The authors adopted a staggered approach to calibrate all the parameters of the finite element model and full-field data of a devised test representative of turbine engine environments.…”
Section: Introductionmentioning
confidence: 99%